2011
DOI: 10.1111/j.1742-6723.2011.01511.x
|View full text |Cite
|
Sign up to set email alerts
|

Burn size estimation in children: Still a problem

Abstract: Inaccurate estimation of burn size remains a problem in children. The persistent miscalculation of burn size might be a result of the various methods employed in assessing burn area, the inclusion of simple erythema and inadequate training or exposure of first responders. Accurate assessment of TBSA-B and burn depth in children remains elusive and would appear to require additional training and education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 20 publications
1
20
0
2
Order By: Relevance
“…The current study revealed that, nurses had incompetent practice about infection control, This result was in harmony with Abdel Kawy (2011), (19) who studied "early management of burn in pediatric age group Cairo University" and reported that, the majority of nurses had unsatisfactory practice about infection control in burn management. This finding may be due to absence of supervision as well as lack of training program which was documented by the fact that, the high percentage of the studied nurses did not receive training about burn management.…”
Section: Abd El-lateef (2011)supporting
confidence: 74%
“…The current study revealed that, nurses had incompetent practice about infection control, This result was in harmony with Abdel Kawy (2011), (19) who studied "early management of burn in pediatric age group Cairo University" and reported that, the majority of nurses had unsatisfactory practice about infection control in burn management. This finding may be due to absence of supervision as well as lack of training program which was documented by the fact that, the high percentage of the studied nurses did not receive training about burn management.…”
Section: Abd El-lateef (2011)supporting
confidence: 74%
“…Inaccuracies in the coding of external cause are possible, as well as in the coding of %TBSA in hospital data 23 . ‐ 25 It has been reported that %TBSA is likely to be overestimated by referring hospitals when compared with assessments in specialist burn units 23 , 24 . We may have underestimated the burden of burn injury hospitalisation in our cohort, as some repeat admissions might have been missed because of differences in external or primary diagnosis coding, and because we restricted our analysis to the first burn injury.…”
Section: Discussionmentioning
confidence: 99%
“…Однако в литературе появля-ется все больше указаний, что ручные методы оцен-ки обожженной поверхности тела содержат ошибки [13][14][15][16]. В ряде публикаций представлены данные, что программы показывают значительно более низ-кие значения, при том что завышение глубины/ размера ожога по расчетам врачей составляло от 50 до 62% [2,4,16,17].…”
Section: дискуссияunclassified
“…Высокое стандартное отклонение наблюдается у пациентов с малыми, разбросанными по телу площадями ожогов; низкое стандартное от-клонение -при несколько больших площадях. Пере-оценка зависит от расположения и степени областей поверхностных ожогов [15,16]. Для ожога средней степени в оценках врачей был выявлен особенно большой разброс отклонений -от 3,5 до 15,3% [16].…”
Section: дискуссияunclassified